Pentingnya Memiliki Soft Skill Bagi Calon Pekerja Sebagai Keterampilan Kesiapan Kerja - Yosi Ragil Cahyono; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
Soft skills are special abilities that can improve a person's work performance and career prospects. These soft skills help students to develop their employability skills and make them confident to work in a performance-oriented work environment as critical lifelong learners. In this regard, it is the obligation of educators to prepare their graduates to be able to compete in the future economic world. This article provides an overview of the increasing concern among employers regarding the soft skills of graduates in the world of work, so that they see the importance of soft skills, soft skills are much sought after by employers, the lack of soft skills in graduates, the lack of soft skills. skills and various aspects of work. soft skills to be taught and assessed by educators. This paper shows that students with soft skills such as positive attitude, effective communication, problem solving skills, etc. Have a greater chance of survival in the critical business world compared to students who do not have these skills.